Pengawasan Bahan Pangan Tidak Layak Edar oleh Badan Pengawasan Obat dan Makanan (BPOM) Kota Batam - Suci Kumala Sari; Timbul Dompak (Universitas Batanghari Jambi, 2023)
The Food and Drug Supervisory Agency (BPOM) is a non-ministerial central government agency in Indonesia, which is based on Presidential Regulation Article 2 No 80 of 2017 which carries out government duties in the field of controlling the distribution of drugs and food throughout Indonesia. Decree of the Head of the Food and Drug Supervisory Agency (BPOM) of the Republic of Indonesia Number 14 of 2014 concerning the organization of work procedures for implementing technical units within the drug and food regulatory agency, a Balai was formed. Food and Drug Supervisory (BPOM) located in every province in Indonesia to facilitate the supervision of drugs and food in the regions. The purpose of this study is first to describe the supervision of BPOM Kepri Batam against illegal drugs and food in Batam City, the two factors that influence BPOM Kepri in controlling illegal drugs and food in Batam City. The research method is qualitative.Data collection techniques are interviews, observation and documentation. Sources of data used are primary data sources which are obtained directly from data sources and secondary data which are obtained indirectly through websites, annual reports, and performance reports. This research was carried out by the Kepri Food and Drug Supervisory Agency (BPOM), business actors and the community. the result of the research is the Supervision of BPOM Kepri on illegal drugs and food in Batam City. The supervision carried out by BPOM Kepri is carried out in two ways, namely pre market and post market supervision, both supervision that is carried out before the product is circulated and before it is circulated, in this case BPOM in conducting technical supervision with 3 (three) lines, namely BPOM as the first line as the government, the second line. producers / distributors and the thirt line of society as control of the performance of BPOM Kepri, especially in Batam City.